Role of Variety Seeking and Perceived Monetary Value on Tourist Intention – a Developing Country Perspective - Joydeep Biswas; Shabbirhusain R. V. (Centre For Tourism Planning and Development, 2020)
The purpose of this study was to investigate the moderating impact of tourist's individual characteristics on the impact of cognitive and affective components of destination image on tourist behavioural loyalty. We specifically explored the moderating role of perceived monetary value that an individual ascribed to a travel destination and his/her variety seeking nature on the intention to return to a destination. Four hundred and thirty-three respondents participated in an online survey. Exploratory factor analysis was used for scale purification. ANOVA was used for hypothesis testing. Hypothesis testing revealed that impact of cognitive and affective image on tourist revisit intentions is strengthened if perceived monetary value of a destination is high while a tourist’s variety seeking behaviour moderates the influences of cognitive image on intention to revisit. The study extends existing literature by highlighting the importance of individual characteristics, especially with reference to a developing country tourist.